Athlete experiences of communication strategies in applied sports nutrition and future considerations for mobile app supportive solutions - Dunne, David Mark; Lefevre-Lewis, Carmen; Cunniffe, Brian; Impey, Samuel George; Tod, David; Close, Graeme Leonard; Morton, James P.; Murphy, Rebecca (Frontiers in Sports and Active Living, 2022)
Aim This study aimed to explore athletes' experiences and opinions of communication strategies in applied sports nutrition, as well as capture suggestions for future mobile app supportive solutions. Methods A qualitative approach was used for this research. Data was generated from semi-structured focus groups (n = 9) with a purposive sample of 41 (male = 24, female = 17) full time professional athletes (mean age 24 ± 4.59) from five sports (football, rugby union, athletics, cycling, and boxing). Data was analyzed using reflexive thematic analysis. Results The analysis identified four higher order themes and five sub themes. Athletes appear dissatisfied with the levels of personalization in the nutrition support they receive. Limited practitioner contact time was suggested as a contributing factor to this problem. Athletes acknowledged the usefulness of online remote nutrition support and reported a desire for more personalized technology that can tailor support to their individual needs. Conclusion Athletes experienced a hybrid human-computer approach that combines in-person and remote digital methods to communicate with and receive information from practitioners. Mobile technology may now afford sports nutritionists with new opportunities to develop scalable solutions to support practice.